Enhancing student employability through urban ecology fieldwork. Issue 1 (1st January 2018) - Peacock, Julie; Bacon, Karen L.
Abstract: Students undertook a one-hour urban ecology activity based on the University of Leeds campus. The aims of the session were (1) to help students to link ecological theory to practice and (2) to encourage students to begin to think about and develop an online professional identity. Students were encouraged to tweet throughout the session and were surveyed four weeks after the session to determine if the aims had been met. A majority of students enjoyed the session and saw the links between the theory and practice of ecology. Most students also identified that an online professional identity is important and something that they should be developing. The session highlights that employability and professional development skills can be introduced to students within a subject-specific context early in their degree programme and still highlight the importance of generic transferable skills related to employability.